The Methods of Control of Stabilized Detonation Location in a Supersonic Gas Flow in a Plane Channel. Issue 7 (19th May 2023) - Levin, Vladimir A.; Zhuravskaya, Tatiana A.
ABSTRACT: Using a detailed kinetic model of chemical interaction, we have studied detonation stabilization in a stoichiometric hydrogen–air mixture flowing at a supersonic velocity into a symmetric plane channel with constriction the outflow section of which exceeds the inflow one. In addition, we examined the possibility of control of stabilized detonation location in the flow. In case of detonation initiation by energy input, the investigation of conditions of formation of a thrust developing flow with a stabilized detonation wave in the channel was conducted. The structure of the stabilized detonation wave was studied. We examined the effect of variations of the inflow Mach number, dustiness of the inflowing gas mixture, and geometric parameters of the channel on stabilized detonation location with the goal of thrust increase. In addition, the possibility of formation of the thrust developing flow with stabilized detonation in the channel without any energy consumption has been detected.